2020
DOI: 10.3390/ani10091522
|View full text |Cite
|
Sign up to set email alerts
|

Internal Teat Sealant Administered at Drying off Reduces Intramammary Infections during the Dry and Early Lactation Periods of Dairy Cows

Abstract: The effect of an internal teat sealant (ITS) on subsequent infection of the mammary gland was evaluated on the following mammary gland health indicators: (a) bacteriological cure of preexisting intramammary infections at drying off, (b) risk of postpartum new intramammary infections (NIMI), (c) cure and risk of new cases of subclinical mastitis (SCM), and (d) risk of postpartum clinical mastitis (CM). A total of 553 cows during late gestation were randomly assigned into two treatment protocols at drying off: (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 37 publications
3
7
0
Order By: Relevance
“…Our study showed that there were no significant differences in odds of clinical mastitis post-calving between the trial groups, which was in agreement with previous studies despite differences in study design [ 10 , 11 ]. Others have reported significant differences in post-calving clinical mastitis between cows treated at dry-off with AB + TS compared to AB only, which could be attributed to differences in herds and their management practices, or to the statistical methods used [ 12 , 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that there were no significant differences in odds of clinical mastitis post-calving between the trial groups, which was in agreement with previous studies despite differences in study design [ 10 , 11 ]. Others have reported significant differences in post-calving clinical mastitis between cows treated at dry-off with AB + TS compared to AB only, which could be attributed to differences in herds and their management practices, or to the statistical methods used [ 12 , 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…agalactiae are recommended to be treated with antimicrobials during lactation (Keefe, 2012), whereas for Strep. dysgalactiae, treatment using dry cow therapy would be more adequate, resulting in cure risk close to 100% (Whist et al, 2007;Freu et al, 2020). Regarding the diagnosis of cows with CM caused by Strep.…”
Section: Discussionmentioning
confidence: 99%
“…Following the infusion of ATB, each teat received ITS and was then submerged in a commercial iodine-based teat dip (1% iodine, Della Barrier, DeLaval, Tumba, Sweden). To ensure that the ITS stayed in the teat canal, the teat base was held with two fingers and no massage was given, as described by previous researchers [ 2 ]. Farm personnel administered both protocols.…”
Section: Methodsmentioning
confidence: 99%
“…Dry cow therapy (DCT) refers to the intramammary administration of antimicrobials, which can be performed either in association with internal teat sealant (ITS) or not, to cure intramammary infections (IMI) acquired during lactation and to prevent the occurrence of new intramammary infections (NIMI) during the dry period [ 1 , 2 ]. Using DCT in all cows (also known as blanket DCT) results in the use of antibiotics (ATB) in healthy cows.…”
Section: Introductionmentioning
confidence: 99%